Learning English Through Real-Life Scenarios: How Task-Based Learning Makes a Difference - Mohd. Rafi Riyawi,; Kalayo Hasibuan, (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Task-Based Learning (TBL) has emerged as an innovative methodology in English language instruction, emphasizing significant communication, practical application, and learner-focused activities. This research examines the practical obstacles to implementing TBL in educational settings, including task design, classroom management, resource constraints, assessment hurdles, teacher readiness, and cultural resistance. Approaches to tackle these difficulties encompass scaffolding approaches, differentiated instruction, teacher professional development, and innovative utilization of available resources. A comparison between TBL and conventional language training methodologies underscores their unique benefits: TBL promotes fluency, engagement, and autonomy, whereas traditional techniques prioritize grammatical precision and regimented learning. The analysis supports a hybrid strategy that integrates the communicative advantages of TBL with the fundamental benefits of older methods to establish a comprehensive language learning framework. Despite its difficulties, TBL possesses transformative potential in augmenting learner motivation, confidence, and practical language abilities, rendering it a significant enhancement to English language instruction. This study suggests that, with careful implementation and stakeholder support, TBL may transform language instruction and equip learners for effective communication in varied circumstances.